OPTIMALISASI PROGRAM AKSELERASI PEMBELAJARAN TAHFIDZUL QUR’AN PADA LEMBAGA MADRASAH IBTIDAIYAH NAHDLATUL ULAMA KECAMATAN LEKOK KABUPATEN PASURUAN - Hamidah; Nailatul Khoiriyah Cholil, M.Pd.I. Naila (Tarbawi : Jurnal Studi Pendidikan Islami, 2024)
This research aims to determine the optimization of the Tahfidzul Qur'an accelerated learning program at the Nahdlatul Ulama' Lekok Madrasah Ibtidaiyah institution in teaching and training students in memorizing the Al-Qur'an in its entirety Apart from that, the aim of this research is to find out how optimal the acceleration program is, the advantages and disadvantages of learning, the impact of the Tahfidzul Qur'an acceleration program with the aim of how optimal the Tahfidzul Qur'an learning acceleration program is at the Nahdlatul Ulama' Lekok madrasah institution.Tahfîz is the process of memorizing the verses of the Koran as a whole and protecting them from forgetting. The hafz is using certain methods for remembering. Since the time of Prophet Muhammad, these methods have largely been followed. Receiving a revelation from Jibril as such. Well, that's how Allah SWT does it. He's determined to preserve the authenticity of the Koran and the tradition that's inherent in Muslims. The study of tahfîz al-Qur'an has so far focused more on field studies in Islamic boarding schools and Al-Qur'an institutions, especially on success factors, systems, infrastructure, teacher qualifications, curriculum and learning outcomes . Thesis: "A comparative study of tahfz al Qur'an's education in Indonesia and Saudi Arabia", 1994). The study of memorization methods was written by Yahyâ bin 6Abd al- Razzâq al-Ghautsani in “Kaifa Tahfaz al-Qur'an; Qawâ„îd Asâsiyyah wa Turuq „Amaliyah (Dâr al- Ghutsân, 2001), but these methods are not written in detail and are very practical. The author therefore seeks to describe the methods of Koranic memorization in a critical manner in his thesis. These methods are talaqqi, tasmî,, ,arad, qirâ'ah fî alsalâh, kitâbah, tafhîm, the method of memorizing alone and memorizing five verses of five verses. In the current era, these methods can be assisted using electronic media such as cassettes, Murattal CDs/memorization programs, recorder types, computers and so on. These methods can be optimally carried out by a person if they pay attention to supporting factors, namely: age, intelligence and cleanliness of heart. These factors really determine how memorizers of the Qur'an use their preferred methods and/or combine several methods according to their intelligence and age, so that all their senses of knowledge can develop dynamically. A qualitative research methodology using descriptive methods, namely the use of studies that produce descriptive data in a form of written or spoken words, is used to carry out such research. The author may get reliable data by selecting such a qualitative method. Judging from the nature of data presentation, the descriptive method is research that does not look for or explain relationships, does not test hypotheses or predictions. The authors conclude that the optimal programme for Tahfizul Qur'an education acceleration in Nahdlatul Ulama Lekokah Ibtidaiyah is an appropriate one based on these results. starting from the initial entry process, carrying out Ubudiyah together in turns, carrying out muraja'ah and carrying out simaan with the tahfidz teacher, learning is different from regular classes, even with a very different return time system